Evidence of apoptosis as an early event leading to cyclophosphamide-induced primordial follicle depletion in a prepubertal mouse model - Hao, Xia; Reyes Palomares, Arturo; Anastácio, Amandine; Liu, Kui; Rodriguez-Wallberg, Kenny A. (Frontiers in Endocrinology, 2024)
The mechanisms leading to ovarian primordial follicle depletion as follows of gonadotoxic chemotherapy with cyclophosphamide, and other cytotoxic drugs, are currently proposed through two main explanatory theories: apoptosis and over-activation. Discrepancies between findings of studies investigating these mechanisms do not allow yet to make firm conclusions. The heterogeneity of cell types in ovaries and their different degrees of sensitivity to damage, cell-cell interactions, periodical follicle profile differences, age-dependent differences, as well as differences in duration exposure to the drugs tested may partially explain discrepancies among studies. This study aimed to dynamically capture the early ovarian response to cyclophosphamide exposure using intact prepubertal mice ovaries in culture as study model, in which most follicles are primordial follicles. Histological and transcriptional analysis of ovaries exposed to the active metabolite of cyclophosphamide 4-hydroperoxycyclophosphamide (4-HC) were carried out via a time-course experiment at 8-24-48 and up till 72 hours. Our results showed a significant decrease in primordial follicle density at 24 hours, along with active DNA damage (TUNEL) and apoptosis signals (cleaved-PARP) in the ovaries. Meanwhile, significant expressional alterations of H2ax, Casp 6, Casp 8, Noxa and Bax also indicated that cyclophosphamide-induced acute ovarian primordial follicle depletion was mainly related to apoptotic pathways. No evidence of follicle activation was found at 24 hours, either through changes in the expression of related genes to follicle activation or in the density of growing follicles. Further validation at protein level in 4-HC-treated prepubertal mice ovaries for 24 hours confirmed these observations.